Solusi Keuangan Syariah Terhadap Pembiayaan Sektor Pertanian untuk Mencapai Sustainable Development Goals - Aini, Rija; K, Kamilah (Ecoplan, 2025)
Islamic finance plays a strategic role in supporting inclusive and sustainable economic development. One important sector that requires attention is the agricultural sector, which directly contributes to the achievement of several SDGs. This research analyzed potential Islamic finance schemes supporting agricultural sector financing and its impact on achieving SDGs. It employed a qualitative method with a literature study approach supported by relevant secondary data. The research investigated journal articles primarily sourced from Google Scholar with a range of research years from 2019 to 2024. As a result, 8 articles were obtained. Meanwhile, secondary data related to Islamic finance was obtained from the official websites of related banks, OJK, and SGIE Report. The results of this study show that Islamic financial schemes that can be a solution are salam financing, mudharabah, musyarakah, and waqf. Salam financing, for example, provides a solution for farmers to obtain working capital at the beginning of the planting season. Meanwhile, mudharabah and musyarakah allow for a fair partnership pattern with risk and profit sharing. On the other hand, waqf, especially productive waqf, offers a long-term orientated scheme to support agricultural infrastructure and farmer empowerment without additional financial burden. The impact of Islamic financing on the SDGs is significant, especially in enhancing resilience, responsible production and consumption, and climate improvement. The results of this study are expected to provide practical recommendations for Islamic finance stakeholders in supporting a sustainable agriculture sector and add insight for readers regarding Islamic finance for the agriculture sector.